Triggering Students' Critical Thinking Through Literary Analysis - Rizka Norsy Ramadhana; Yusuf Al Arief; Eka Puteri Elyani; Fatchul Mu’in (UMBanjarmasin, 2022)
Abstract Through literary analysis, students can obtain critical thinking skills. Literature is a branch of art that undergoes a growth process in line with the passage of time and the development of people's minds. Having literature in the teaching and learning process can create a critical thinking process. Students will practice expressing opinions, concluding, explaining cause-and-effect relationships, comparing facts, and applying the ideas they have gained from literature to new situations. This research used descriptive quantitative. The sample of this study is students of the English Language Education Study Program batch 2018 that have taken literary analysis classes. The empirical data needed in this research are observation of implementation of literary analysis in the classroom and questioners of classroom reflection based on critical thinking indicators. The research findings showed that the implementation of literary analysis learning in the classroom through observation sheets has been going well. It found that students conduct 80% of the critical thinking skills indicators. In addition, analyzing literary works can trigger students to think critically to the level of HOTS (High Order Thinking Skills) because students have entered stage 6 in the critical thinking sequence, namely